A Call to Arms for the Earth. Environmental Poetry in Aotearoa New Zealand and the Pacific Islands: The Case of the Anthology No Other Place to Stand (Altre Modernità, 2024)
Poetry is a major artistic expression in New Zealand and Pacific culture, including a longstanding tradition of indigenous oral literature. Besides its many functions, it can also have a crucial militant role. In the present climate emergency, the potential of oral and written poetry for environmental activism has been rediscovered: “poet-performers” have risen as militant figures that write verses and act them out on websites, during public performances and in important political venues. The effects of global warming are dramatically real in the Pacific region, especially in consequence of the sea-level rise that has caused the flooding of many atolls and is threatening the survival of populations and cultures. Aotearoa has always been sensitive to environmental problems, also thanks to the prominent voice of the Māori minority in the country’s politics. It is thus not surprising the recent publication of No Other Place to Stand (2022), the first New Zealand poetry anthology to deal with climate issues from a specifically New Zealand and Pacific perspective. The book forms a dedicated platform for creative work in response to the climate crisis. Half of the contributors are indigenous and a good number under thirty, giving voice to the people of the land and to those with the most at stake for their futures. My article will provide a critical analysis of the volume against the Pacific cultural and political background.